Preparation and Evaluation of Modified Proniosomal Gel for Localised Urticaria and Optimisation by Statistical Method - B. Rita, P. K. Lakshmi (Journal of Applied Pharmaceutical Science)
The objective of the study was to formulate a modified proniosomal gel (HMPG) of hydroxyzine hydrochloride. HMPG formulations were prepared by coacervation phase separation technique with different combination of non-ionic surfactants (Tweens and Spans) with phospholipids such as phospholipon 80H and 90H. Taguchi design of experiments was used to optimize the various formulation variables. The optimized HMPG formulations were evaluated for entrapment efficiency, vesicle size, SEM, FTIR, in vitro diffusion study, exvivo permeation, skin deposition, skin irritation and stability studies. Tween 60: Span 40 with Phospholipon 90 H formulation (H90-5) showed the highest entrapment efficiency of 94.8%. In vitro drug release was found to be as low as 1.33%, exvivo drug permeation into the skin showed only 1.18 % and drug deposition in the SC was found to be 88.24% at the end of 24 hr. The H90-5 formulation was found to be stable for three months at refrigeration temperature. The results revealed that modified proniosomal formulations of hydroxyzine hydrochloride were suitable for topical drug delivery system for the treatment of localized urticaria.
Keywords: Modified proniosome, Hydroxyzine hydrochloride,Provesicular delivery, Phospholipons,Nonionic surfactants